Infant formula crisis in China: A cohort study in Sichuan province - Tang, L.; Binns, Colin; Lee, A. (International Center for Diarrhoeal Disease Research, 2015)
China has become the largest market of infant formula in the world. The consumption of infant formula is widespread across the country. This study investigated the opinions of Chinese mothers on infant formula. A prospective cohort study (n=695) was undertaken in 2011 in Sichuan province of China two years after the melamine scandal. Infant-feeding practices and mothers' opinions on infant formula-use were documented in detail. A total of 674 mothers (97%) had initiated breastfeeding by discharge. Of the 21 mothers who did not commence breastfeeding, 13 made a decision to exclusively feed their babies with infant formula because of hepatitis B virus infection. Nearly 70% of newborns received infant formula as their first feed, and the prevalence increased to 88% within one month. Having insufficient breastmilk was perceived by the majority (77%) of mothers as the reason behind infant formula feeding. About half (46%) of the mothers agreed with or were ambivalent that infant formula feeding does not reduce their breastmilk production. More than one-third (38%) of women thought that formulafed infants sleep longer at night than those who are breastfed. In addition, this perception was positively associated with the use of formula within one month postpartum (p=0.003). In conclusion, mothers' opinions appear to influence the use of infant formula in China. There is a need for further education on breastfeeding and infant-feeding options to maintain and improve breastfeeding outcomes in China.